2021
DOI: 10.3389/fmicb.2021.617710
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Transcriptional Changes During Infection of Meloidogyne incognita Eggs by the Egg-Parasitic Fungus Purpureocillium lilacinum

Abstract: The egg-pathogenic fungus Purpureocillium lilacinum parasitizes on nematode eggs, and thus, it is used as a good biocontrol agent against plant root-knot nematodes. However, little is known about the transcriptional response of P. lilacinum while infecting nematode eggs. This study presents the whole transcriptome sequencing of P. lilacinum and transcriptome-wide gene expression analysis of P. lilacinum upon infecting the eggs of Meloidogyne incognita compared to non-infecting controls. A transcriptomic librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…In particular, it has been demonstrated that cuticle-degrading protease, chitinase, and serine protease, play important roles in degrading nematode eggshells [41][42][43] and thereby P. lilacinum parasitizes M. incognita. In addition, another studies reported that the proteins with CFEM (common in fungal extracellular membrane) domains were up-regulated during the infection of nematode eggs and suggested that the CFEM proteins is important for the recognition of nematode-eggs by the fungus [44,45]. Recently, P. lilacinum was shown to produce secondary metabolites (e.g., leucinostatins, paecilomide, and acremoxanthones) that cause strong mortality and inhibit nematode reproduction.…”
Section: Plos Onementioning
confidence: 99%
“…In particular, it has been demonstrated that cuticle-degrading protease, chitinase, and serine protease, play important roles in degrading nematode eggshells [41][42][43] and thereby P. lilacinum parasitizes M. incognita. In addition, another studies reported that the proteins with CFEM (common in fungal extracellular membrane) domains were up-regulated during the infection of nematode eggs and suggested that the CFEM proteins is important for the recognition of nematode-eggs by the fungus [44,45]. Recently, P. lilacinum was shown to produce secondary metabolites (e.g., leucinostatins, paecilomide, and acremoxanthones) that cause strong mortality and inhibit nematode reproduction.…”
Section: Plos Onementioning
confidence: 99%
“…Purpureocillium species Microorganisms 2024, 12, 1041 2 of 11 employ unique biological mechanisms, such as secreting enzymes capable of degrading nematode eggshells, effectively diminishing nematode populations and alleviating their damage to crops [10]. This natural and efficient control strategy offers a sustainable alternative to chemical pesticides, enhancing the sustainable development of agricultural ecosystems [11]. Additionally, P. lilacinum exhibits significant insecticidal activity and shows potential for effectiveness against a diverse array of pests.…”
Section: Introductionmentioning
confidence: 99%